(untitled) (Analele Universității București.Filosofie, 2025)
This paper explores the concepts of nation and nationalism in Niccolò Machiavelli’s The Prince, with a particular focus on the introduction of plurinationalism. While Machiavelli’s final chapter, An exhortation to liberate Italy from the Barbarians, has traditionally been the focal point for discussions on his nationalist views, this study shifts the lens to examine how Machiavelli’s strategies for maintaining control over diverse territories reveal implicit notions of nation and nationalism. By analysing the third chapter, Concerning mixed principalities, this paper highlights Machiavelli’s understanding of the challenges posed by ruling over territories with different languages, customs and laws. The strategies of residing in newly acquired territories and establishing colonies are presented as methods for fostering loyalty and integration, thereby addressing the complexities of a plurinational principality. This study not only expands the traditional interpretations of Machiavelli’s nationalism but also emphasises the relevance of his insights in contemporary discussions on governance and statecraft in a multicultural and multiethnic context. Through this perspective, The Prince is reaffirmed as a timeless guide on the pragmatic exercise of power.